Performance of Automotive Industry under Financial Crisis - Cheng, Xiaomeng (2012)
Since the financial crisis, automobile industry faces severe problems such as sale decline and cash shortage. Some corporations such as General Motors also went to bankrupt. The whole industry was under financial distress and this also affected other related industries such as part manufacturers and suppliers. Most literatures investigated the industry performance by measures such as sale and production volume, export record or GDP contribution. Few of them examine the industrial performance using financial ratio analysis or highlight the key financial indicators in the automobile industry. There are a number of financial ratios that are more important than the others for different industries. This research applies factor analysis to determine the key financial indicators extracted from some financial ratios to analyse the global automobile industry. Four financial indicators are crucial in auto industry and their importance are ranked as ‘Liquidity’, ‘Activity management’, ‘Cash flow’ and ‘Profitability’. It also applies the four indicators to General Motors bankruptcy case and examines reasons of a specific company failure. This study contributes a lot to previous literatures as an empirical example in areas such as factor analysis, performance measure, crisis theory and bankruptcy discuss.